Negotiating with the 'Archenemy': Ethics of Croatian and Slavonian Nobility Confronted with the Ottomans - Štefanec, Nataša (2012)
In the 16th and partly in the 17th century, Croatian and Slavonian nobility often threatened with surrender to the Ottomans, especially in times of fierce combats. Other social strata, peasants and military would even voluntarily move and change sides accepting the jurisdiction of a gentler lord in an attempt to survive. Interactions with the Ottomans were, therefore, not reduced to confrontation. Actually, conditioned by an attempt to avoid devastation and annihilation there existed various types of more complex interactions among the opposing sides. They were challenging the paradigm of antemurale Christianitatis. This paper would address two main problems. Firstly, were the Ottomans the main Croatian-Slavonian early modern adversary, the archenemy of Christianity? Secondly, were the threats with surrender to the Ottomans a plausible political option in the Croatian-Slavonian Kingdom? For this purpose, several contexts should be reconstructed and presented. First, official political-military strategies of Habsburgs, Croatian-Slavonian and Inner-Austrian Estates towards the Ottomans. Second, everyday practices of interaction with the Ottomans on the Military Border. Third, who and in which way negotiated with the Ottomans? Fourth, were the Ottomans the only Christian adversary in the region?
Objavljivanje rada u zborniku radova predviđa se tijekom 2011. godine. Urednici: Robert Born, Sabine Jagodzinski
Projekt MZOS
ENG